Longfellow Redevelopment: Kansas City, Missouri - Amy Fountain; Robert Frye (Oz, 1984)
Throughout the past fifty years, the steady exodus of middle income home owners from urban areas has caused a growing void in the inner city. However, during the last decade this migratory trend has shown signs of reversing…